Demographic Determinants of Potential Labour Force Substitution in Poland and Europe - Kowaleski, Jerzy; Majdzińska, Anna (Olsztyn Economic Journal, 2017)
This article presents the levels of the potential labour force in European countries resulting from the inflow of young cohorts into the age group 15+ and the outflow of people aged 65 years and older from the labour market. The purpose of the analysis is to assess the replacement of the present and future potential labour force in European countries, particularly in Poland. This study is at the level of voivodeships and poviats.